Bortezomib prevents acute doxorubicin ovarian insult and follicle demise, improving the fertility window and pup birth weight in mice. - Elon C Roti Roti; Ashley K Ringelstetter; Jenna Kropp; David H Abbott; Sana M Salih (PLoS ONE)
Increasing numbers of female patients survive cancer, but succumb to primary ovarian insufficiency after chemotherapy. We tested the hypothesis that Bortezomib (Bort) protects ovaries from doxorubicin (DXR) chemotherapy by treating female mice with Bort 1 hour prior to DXR. By preventing DXR accumulation in the ovary, Bort attenuated DXR-induced DNA damage in all ovarian cell types, subsequent γH2AFX phosphorylation, and resulting apoptosis in preantral follicles. Bort pretreatment extended the number of litters per mouse, improved litter size and increased pup weight following DXR treatment, thus increasing the duration of post-chemotherapy fertility and improving pup health. As a promising prophylactic ovoprotective agent, Bort does not interfere with cancer treatment, and is currently used as a chemotherapy adjuvant. Bort-based chemoprotection may preserve ovarian function in a non-invasive manner that avoids surgical ovarian preservation, thus diminishing the health complications of premature menopause following cancer treatment.